Late Cretaceous planktonic foraminiferal bioevents in the Tethys and in the Southern Ocean record: an overview - M.R. Petrizzo (The Journal of Foraminiferal Research, 2003)
The Late Cretaceous planktonic foraminiferal distribution recorded at several drill sites (Deep Sea Drilling Project and Ocean Drilling Program) in the South Atlantic and south Indian Ocean and from sediment outcrops in the Tethyan region (Gubbio and El Kef) have been analyzed in order to investigate the presence of a similar sequence of bioevents occurring at low, middle, and high latitude. Comparative analysis highlights the co-occurrence of several bioevents; some of them are isochronous bioevents occurring in the Tethys and in the Southern Ocean record, whereas others are diachronous across latitudes but can be used for correlation at regional scale, as they show the same stratigraphic distribution in the South Atlantic and Indian Ocean record. Isochronous bioevents are the first and the last occurrence of Helvetoglobotruncana helvetica, and the first appearance of Falsotruncana maslakovae in the lower-middle Turonian. The first occurrence of Heterohelix papula in the Southern Ocean sites, correlated with the first occurrence of large heterohelicids in the Tethyan area, allows the Coniacian/Santonian boundary to be identified. The most reliable bioevents useful for correlation at a regional scale in the Southern Ocean record are the last occurrence of the marginotruncanids in the upper Santonian, the first and the last occurrence of Globigerinelloides impensus from the uppermost Santonian to upper Campanian, the first occurrence of Heterohelix rajagopalani in the middle-upper Campanian, and the appearance of Abathomphalus mayaroensis in the lower Maastrichtian.